The Beauty of Wabi Sabi as the Spirit of Life of the Oldman in Japanese Fairytale - Ainie, Isnin; Pujimahanani, Cahyaningsih; Aulia Mareta, Syifa (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2023)
Wabi sabi is one of Philosophy in Japan. It’s about appreciation to the beauty of imperfection. Wabi sabi can be found in so many aspects in Japanese people’s life such as chanoyu, ikebana, haiku, or fairytale of Japanese children. This article aims to know how the oldman gets the spirit of life by wabi sabi to cheer his life. Hanasaka Jiisan is used in this research as a source of data. The result is the beauty of wabi sabi is appeared by the oldman’ house, the falling leaves, the dead trees, and the falling flowers. Furthermore, wabi sabi as the spirit of life can be found in the old man who lives with his wife, the old man who takes care of a dog, the old man who takes the ash of mortar home, and the old man who throws ash all over the dead trees and it makes the lord of local castle so happy.